The acute management of ankle fractures (Augment) study: A prospective trainee led national collaborative audit of the Boast 12 guidelines. Issue 5 (October 2021) - Fennelly, Joseph T.; Gourbault, Lysander J.; Stedman, Tobias; Price, Michael J.; Ward, Alex E.; ,; Yousuf, Umar; Senthilkumaran, Sriskandarasa; Kumar, Vish; Korde, Vinayak; Baigent, Thomas; Mahmood, Fahd; et al.
Abstract: Background: Ankle fractures are one of the most common fractures in adults aged 20–65 years. The British Orthopaedic Association (BOA) and British Orthopaedic Foot and Ankle Society (BOFAS) jointly produced Standards for Trauma (BOAST) BOAST 12, with the aim of reducing morbidity by standardising care of these injuries. The primary aim of the AUGMENT study was to determine the extent and clinical effect of variation from BOAST 12. Methods: AUGMENT was a multi-centre prospective trainee led audit of consecutive patients presenting with an ankle fracture within a four-week period. Data were collected on patient demographics, comorbidities, management and 12-week outcome. The BOAST 12 standards were divided into four subgroups; documentation, imaging, management and follow-up. Percentage compliance with each subgroup was analysed. A multivariate logistic regression analysis was used to determine impact of overall compliance on likelihood of discharge in follow-up period. Findings: 971 patients were included across 52 sites. The overall rate of BOAST 12 compliance was 41.7%. Variations in practice were observed in clinical documentation, especially of neurovascular status, (40.7%) and VTE assessment (61.5%). Patient management compliance with all 16 of the BOAST 12 standards was associated with a higher rate of discharge during the 12-week follow-up period ( p = 0.005). Conclusion: AUGMENT has demonstrated that the management of ankle fractures is variable across the UK. Over half of patients had aspects of their care that were not BOAST 12 compliant. When compliance was observed, it was associated with earlier discharge from orthopaedic care. Highlights: This study focussed on the management of ankle fractures by 52 sites across the UK. This is the only study which has assessed the clinical impact of BOAST 12 guidance. Compliance with BOAST 12 is associated reduced follow-up requirements.